Light and electron microscope studies on the toxic effect of Salmonella 3,10:r cell-free extract on rabbit ileum - YASHROY, RAKESH C (The Indian Journal of Animal Sciences, 2013)
Effect of cell-free extract of Salmonella 3, 10:r organisms on the rabbit ileum was studied 18 hr after treatment by light and electron microscopy. Light microscopic examination revealed severe inflammatory conditions with thickened mucosa, congested blood vessels and focal mononuclear cell infiltration. The mucosal glands showed hyperactivity. The lining epithelium revealed hyperplastic changes and the superficial cell layer appeared denuded at places. Under the transmission electron microscope. the lining epithelial cells at places showed degeneration and accumulation, of membranous bodies. A number of white cells such as macrophages.lymphocytes and neutrophils were also identified as infiltrating the treated ileum. apparently involved in the detoxification process.